Campur Kode dan Alih Kode pada Caption di Akun Instagram @Sunda_Humor: Analisis Sosiolinguistik Berbasis Mini Korpus: Penelitian - Maudy Sugihartini (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The process of communication and social interaction can lead to a speaker's tendency to utilize the potential of language variations. Code switching and code mixing are one of the language variations to maintain togetherness in their community, this is the subject of sociolinguistic studies on the topic of code switching and code mixing analysis. Code switching and code mixing are the replacement of the use of a particular language or language variety into another language. This study aims to describe the forms of code switching and certain forms of code mixing found in social media Instagram in the captions of the @sunda_humor account. This research method uses qualitative and quantitative descriptive methods. The data in this study are in the form of language use in the captions on the @sunda_humor Instagram account. The form of the data is in the form of data that has been processed using a corpus tool from the Sketch Engine website. The results of the corpus data were processed using the Scrapper application and entered into Sketch Engine. The data were entered into Sketch Engine and analyzed for code mixing, code switching, and the frequency of the resulting Sundanese language data. The results of the study indicate that the analysis of the forms of code switching that appear in the @sunda_humor Instagram captions is a form of code switching from Sundanese to Indonesian and from Indonesian to Sundanese. The forms of code mixing that emerge include Sundanese into Indonesian, Indonesian into Sundanese, and English.